Management of Inflammatory Bowel Disease - Stephanie Chandra; Marcellus Simadibrata (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2014)
Inflammatory bowel disease (IBD) is an inflammatory disease, which involves the digestive tract with still unknown definite etiology. IBD cases are frequently underdiagnosed or even overdiagnosed. Delay in diagnosis often happen due to the unspecific intermittent symptoms. Principally, treatment of IBD is targeted to acute episodes and maintenance of therapy during remission phase. First line therapy drugs include 5-acetil salicylic acid (5-ASA) and corticosteroids are systemic and topical. If failed, then second line therapy, which has immunosuppressive characteristic, is given such as: 6-mercaptopurine, azathioprine, cyclosporine, methotrexate, and anti-TNF (infliximab). Efforts to prevent recurrent inflammation in IBD are to maintain the remission phase as long as possible. Surgery management may be considered if conservative of pharmacological treatment fails or complication happens. Keywords: inflammatory bowel disease, management, treatment